The Influencing Factors of Superstar Learning System Satisfaction of Students Majoring in Environmental Design: A Case Study of Normal Universities in Sichuan Province - Yu, Bi (Scholar: Human Sciences, 2025)
Purpose: This study aimed to explore the satisfaction and attitude of environmental design students in Sichuan Normal universities when using the superstar learning system in a blended learning environment. The conceptual framework contains information quality, system quality, perceived usefulness, perceived ease of use, perceived enjoyment, attitude and satisfaction. Research design, data, and methodology: The researchers conducted a detailed survey of the student population, using questionnaires to collect data. The subjects of this survey are mainly undergraduates majoring in environmental design from three universities in Sichuan, namely Leshan Normal University, China West Normal University, and Mian Yang Teachers’ College. The collected data was analyzed by rigorous confirmatory factor analysis and structural equation modeling to verify the fit of the study model and determine the causal relationship between the variables. Results: Information quality and system quality significantly impact perceived usefulness. Perceived ease of use significantly impacts attitude and satisfaction. Perceived usefulness has a significant impact on attitude, and satisfaction. In addition, perceived enjoyment has a significant impact on satisfaction. Conclusions: This study provides valuable guidance for improving undergraduate educational practice and, at the same time, helps to develop policies and strategies to promote the effective integration of education, technology, and management.